Efficacy and safety of canakinumab in adolescents and adults with colchicine-resistant familial Mediterranean fever. Issue 1 (December 2015) - Gül, Ahmet; Ozdogan, Huri; Erer, Burak; Ugurlu, Serdal; Kasapcopur, Ozgur; Davis, Nicole; Sevgi, Serhan
Abstract Introduction This open-label pilot study aimed to investigate the efficacy of canakinumab in colchicine-resistant familial Mediterranean fever (FMF) patients. Method Patients with one or more attacks in a month in the preceding 3 months despite colchicine were eligible to enter a 30-day run-in period. Patients who had an attack during the first run-in period advanced to a second 30-day period. At the first attack, patients started to receive three canakinumab 150 mg subcutaneous injections at 4-week intervals, and were then followed for an additional 2 months. Primary efficacy outcome measure was the proportion of patients with 50 % or more reduction in attack frequency. Secondary outcome measures included time to next attack following last canakinumab dose and changes in quality of life assessed by SF-36. Results Thirteen patients were enrolled in the run-in period and 9 advanced to the treatment period. All 9 patients achieved a 50 % or more reduction in attack frequency, and only one patient had an attack during the treatment period. C-reactive protein and serum amyloid A protein levels remained low throughout the treatment period. Significant improvement was observed in both physical and mental component scores of the Short Form-36 at Day 8. Five patients had an attack during the 2-month follow-up, occurring median 71 (range, 31 to 78) days after the last dose. Adverse events were similar to those observed in the previous canakinumab trials. Conclusion Canakinumab was effective at controlling the attack recurrence in patients with FMF resistant to colchicine. Further investigations are warranted to explore canakinumab's potential in the treatment of patients with colchicine resistant FMF. Trial registration ClinicalTrials.govNCT01088880 . Registered 16 March 2010.